(untitled) (Journal of Agriculture & Rural Development, 2008)
HIV/AIDS spreads so quickly and so destructively that it supersedes all disasters ever attacks human civilization. No branch of scientists can declare them aloof or abstain from it. So the agriculturists are very closely concern with its research-issues, nutritional remedies and agro-based care. We know, HIV stands for human immunodeficiency virus. It is the virus that causes AIDS. A member of a group of viruses called retroviruses, HIV infects human cells and uses the energy and nutrients provided by those cells to grow and reproduce. AIDS stands for acquired immunodeficiency syndrome. It is a disease in which the body’s immune system breaks down and is unable to fight off infections, known as "opportunistic infections," and other illnesses that take advantage of a weakened immune system. Opportunistic infections are various in types and it needs not only the care from health professionals rather it deserves agriculturists, nutritionists and social scientists to combat together. When a person is infected with HIV, the virus enters the body and lives and multiplies primarily in the white blood cells. These are immune cells that normally protect us from disease. The hallmark of HIV infection is the progressive loss of a specific type of immune cell called T-helper, or CD4 cells. As the virus grows, it damages or kills these and other cells, weakening the immune system and leaving the person vulnerable to various opportunistic infections and other illnesses ranging from pneumonia to cancer. Understanding how the human immunodeficiency virus (HIV) works inside the human cell gives all scientists important ways about how to attack it at its most vulnerable points and clues to start research. Knowing the secrets of how the virus functions and reproduces itself – a process called its âlife-cycle’- can help scientists design new drugs and nutritional supplements those are more effective at suppressing HIV and support the affected lives. This study will draw a clear and easy-to-understand picture for every scientist, obviously the agriculturists too, being alert and keeping their lives safe from this fatal conjugation of HIV and help to invent natural and/or plant remedies to prevent or suspend HIV’s aggression, as long as we concern. Key words: HIV, AIDS, retro virus, HIV viral transformation. DOI = 10.3329/jard.v5i1.1473 J Agric Rural Dev 5(1&2), 157-166, June 2007